Evaluation of the universal immunization program and challenges in coverage of migrant children in Haridwar, Uttarakhand, India - Latika Nath; Prabhdeep Kaur; Saurabh Tripathi (Wolters Kluwer Medknow Publications, 2015)
Background: Studies show that immunization among migrant children is poor. India has a dropout rate of 17.7% between Bacillus Calmette-Guιrin (BCG) and measles (District Level Household Survey (DLHS)-3). Haridwar district had the highest dropout rate of 27.4% from BCG to diphtheria, pertussis, and tetanus (DPT) 3 (DLHS-3) in Uttarakhand. We evaluated the Universal Immunization Programme (UIP) among migrants in Haridwar in two blocks. Materials and Methods: We developed input, process, and output indicators on infrastructure, human resources, and service delivery. A facility, session site and cross-sectional survey of 180 children were done and proportions for various indicators were estimated. We determined factors associated with not taking vaccination using multivariate analysis. Results: We surveyed 11 cold chain centers, 25 subcenters, 14 sessions, and interviewed 180 mothers. Dropouts were supposed to be tracked using vaccination card counterfoils and tracking registers. The dropout rate from BCG to DPT3 was 30%. Lack of knowledge (adjusted odds ratio (AOR) 6.6,95% confidence interval (CI) 2.6-16.7), mother not being decision maker (AOR 4.0,95%CI 1.7-9.2), lack of contact by Accredited Social Health Activist (ASHA; AOR 3.0,95%CI 1.1-7.7), not being given four post-vaccination messages (AOR 7.7, 95% CI 2.9-20.2), and longer duration of stay in Haridwar (AOR 3.0 95% 1.9-7.6) were risk factors for nonimmunization. The reasons stated by mothers included lack of awareness of session site location (67%) and belief that child should only be vaccinated in their resident district (43%). Conclusions: There was low immunization coverage among migrants within adequate supervision, poor cold chain maintenance, and improper tracking of dropouts. Mobile immunization teams, prelisting of migrant children, and change in incentives of ASHAs for child tracking were needed. A monitoring plan for sessions and cold chain needed enforcement.